Tradition of Sesaji Rewandaat Goa Kreo as local wisdom - Sifa Destry Fauzia; Wakit Abdullah; Dwi Purnanto (Indonesian Journal of Applied Linguistics, 2022)
Sesaji Rewanda tradition is a ceremonial ritual performed by the Gunungpati community in Goa Kreo which is an annual event on the fifth day of Shawwal a month in the Islamic calendar. The ritual ceremony of Sesaji Rewanda is a symbol of respect for the ancestors of the monkeys who had helped Sunan Kalijaga when taking teak wood to be used as the main pillar of the 'saka guru' at the Great Mosque of Demak. This study used descriptive methods with qualitative study forms. The data collection in this study utilized participation observation techniques, in-depth interviews, library studies, and documents. The data obtained were analyzed with an ethnolinguistic approach, then the data analysis technique was completed by ethnographic analysis methods covering domains, taxonomy, and components. In addition, informal and formal methods were applied in presenting data. The results of the study obtained the use of the term in the tradition of Sesaji Rewanda in Gunungpati. The terms used in traditional rituals are classified in monomorphemic and polymorphemic forms (fixation and composition). Through an ethnolinguistic approach, the traditional term Sesaji Rewanda contains lexical and cultural meanings. The mindset of the Gunungpati community is reflected in the terms used in the ritual tradition of Sesaji Rewanda. The use of terms in the lexicon of Sesaji Rewanda can be put as a guide or paradigm of life in behaving and living by the Gunungpati community.